Association Between Left Atrial Abnormality on ECG and Vascular Brain Injury on MRI in the Cardiovascular Health Study. Issue 3 (March 2015) - Kamel, Hooman; Bartz, Traci M.; Longstreth, W.T.; Okin, Peter M.; Thacker, Evan L.; Patton, Kristen K.; Stein, Phyllis K.; Gottesman, Rebecca F.; Heckbert, Susan R.; Kronmal, Richard A.; Elkind, Mitchell S.V.; Soliman, Elsayed Z.
Abstract : Background and Purpose—: Emerging evidence suggests that atrial disease is associated with vascular brain injury in the absence of atrial fibrillation. Methods—: The Cardiovascular Health Study prospectively enrolled community-dwelling adults aged ≥65 years. Among participants who underwent MRI, we examined associations of ECG left atrial abnormality with brain infarcts and leukoaraiosis. P-wave terminal force in lead V1 was the primary measure of left atrial abnormality; P-wave area and duration were secondary predictors. We excluded participants with atrial fibrillation before or on their index ECG. Primary outcomes were incident infarcts and worsening leukoaraiosis from initial to follow-up scan ≈5 years later. Secondary outcomes were prevalent infarcts and degree of leukoaraiosis on initial MRI. Relative risk (RR) and linear regression models were adjusted for vascular risk factors. Results—: Among 3129 participants with ≥1 scan, each SD increase in P-wave terminal force in lead V1 was associated with a 0.05-point (95% confidence interval [CI], 0.0003–0.10) higher baseline white matter grade on a 10-point scale. P-wave terminal force in lead V1 was associated with prevalent infarcts of any type (RR per SD, 1.09; 95% CI, 1.04–1.16) and more so with prevalent nonlacunar infarcts (RR per SD, 1.22; 95% CI, 1.08–1.38). Among 1839 participants with 2 scans, P-wave terminal force in lead V1 was associated with worsening leukoaraiosis (RR per SD, 1.09; 95% CI, 1.01–1.18), but not with incident infarcts (RR per SD, 1.06; 95% CI, 0.93–1.20). Sensitivity analyses adjusting for incident atrial fibrillation found similar results. P-wave area and duration were not associated with outcomes. Conclusions—: ECG left atrial abnormality is associated with vascular brain injury in the absence of documented atrial fibrillation.